3D bioprinting vascular networks in suspension baths. (February 2023) - Li, Shuai; Jin, Jiale; Zhang, Chengran; Yang, Xue; Liu, Yihao; Lei, Pengfei; Hu, Yihe
Highlights: Vascular networks play a vital role in maintaining cell viability in engineered tissues. Suspension bath-based bioprinting shows great potential of fabricating biomimetic vascular networks. Strategies of current suspension bath-based bioprinting techniques are discussed. Pros and cons of methods and materials used in the suspension bath-based bioprinting for fabricating vascular networks are discussed. Trends and future perspectives of the suspension bath-based bioprinting are summarized. Abstract: Fabricating engineered tissues with vascular networks to supply cells with oxygen and nutrients is critical for successful implantation. Cells are encapsulated in the engineered tissues during the fabrication process for a specific goal. Vascular networks that can maintain cell viability during culturing and after implantation can be included during the biomanufacturing process. For better mimicking their native counterparts, the vascular networks need to be highly organized with heterogeneous structures to allow nutrients to reach all of the cells. Many approaches have been explored to fabricate vascular networks for tissue regeneration due to the importance of vascularization for preserving cell viability and tissue function in vivo . Among them, suspension bath-based 3D bioprinting has shown excellent potential for fabricating biomimetic vascular networks. This review will give an overview of recent efforts of 3D bioprinting vascular networks in suspension baths. Finally, future perspectives will be proposed to fabricate vascular networks with optimal structure and biological function by 3D bioprinting in suspension baths. Graphical abstract: Image, graphical abstract